Effect of fat soluble antioxidant in vegetable oils on acrylamide formation in french fries and chemical model system - Kamarudin, Siti Asiah (2017)
Acrylamide, a carcinogen is usually generated in carbohydrate rich heated foods. Among the parameters affecting the concentration of acrylamide in foods, the effect of fat soluble antioxidants has not yet been elucidated satisfactorily. The objective of this study was first to evaluate the effect of fat soluble antioxidants in frying oil on the formation of acrylamide in French fries. Three vegetable oils, having different fat soluble antioxidant content, were selected, and par-fried potato strips were fried in these oils, monitoring the concentration of acrylamide in French fries at different times (frying temperature at 180 °C) and during 10 consecutive frying sessions. The second objective was to evaluate the inhibitory activity of fat soluble antioxidants against the formation of acrylamide in chemical model system. Two chemical model reactions were performed. One was using different oil blends of red palm oil and another was using different vegetable oils. Different oil blends of red palm oil were prepared by blending 10%, 20% and 30% of red palm oil (industrial grade) with canola oil, respectively. Three different vegetable oils were used, namely commercial red palm oil (Carotino), yellow palm oil and corn oil. Vitamin E content in different oil blends of red palm oil and different vegetable oils were determined. Fat soluble antioxidant in vegetable oils affects the formation of acrylamide in French fries, especially when prolonged frying time was used under consecutive frying sessions. Acrylamide concentration in French fries decreased with increasing number of frying and significantly dropped to the lowest level at 524 μg/kg after 10th frying using red palm oil. However, no significant effect of different frying conditions on the formation of acrylamide in French fries for all types of oil was observed. Antioxidant in vegetable oils also affects the formation of acrylamide in chemical model system. Acrylamide concentration significantly increased as percentage of red palm oil increased from 10% to 20%, but later significantly decreased as percentage of red palm oil increased to 30% in oil blends. The lowest acrylamide concentration was found in chemical model system using yellow palm oil. The role of yellow palm oil in reducing acrylamide formation is more obvious in chemical model system compared to food system. Therefore, the usage of yellow palm oil in addition to red palm oil can be proposed as a good mitigation strategy to reduce acrylamide formation.